Hubungan Pola Asuh Orang Tua dalam Penggunaan Gadget dan Pola Tidur dengan Kualitas Tidur Anak Sekolah Dasar di SDN 3 Baureno - Miftahul Jannah (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Children who live in today's era have the characteristic that the behavior of dependence on the internet is very high, so it requires supervision from parents to monitor and control their children's time when playing gadgets. This behavior eventually causes the main problem of sleep quality related to parenting and children's sleep patterns. The purpose of this study was to determine the relationship between parenting patterns in gadget use and sleep patterns with the quality of sleep of elementary school children at SDN 3 Baureno. This research design used a cross sectional approach, a population of 30 children at SDN 3 Baureno, which was taken by total sampling technique. Data were taken using a questionnaire which was analyzed using the Spierman Rho Test with a significance level of p = 0.05. The results showed that almost most (76.7%) parents gave permissive parenting, most children (60%) experienced disturbed sleep patterns, and most children (53.3%) had poor sleep quality. While the statistical test obtained the value of r =0.369 p=0.023 (p<0.05) which means there is a relationship between parenting patterns in the use of Gadgets with the quality of sleep of elementary school children and obtained the value of r =0.462 p=0.013 (p<0.05) which means there is a relationship between sleep patterns with the quality of sleep of elementary school children. Parents should pay more attention to how to properly use Gadgets in children with the right duration so that sleep patterns are more regular and uninterrupted and good sleep quality.